Effect of Temperature on the Thermal Conductivity of Rocks and Its Implication for In Situ Correction - Chi Chen; Chuanqing Zhu; Baoshou Zhang; Boning Tang; Kunyu Li; Wenzheng Li; Xiaodong Fu (Geofluids)
Detailed knowledge of the effects of temperature on the thermal conductivity (λ) of rocks is essential for investigating the geothermal regime of basins and their thermal evolution. In this study, the λ of four rock types (carbonate, clastic, intrusive, and volcanic rocks) were measured at temperatures of 25°C, 50°C, 100°C, 150°C, 200°C, 250°C, and 300°C using the Transient Plane Source (TPS) approach, which is accurate to ±3%. Experimental results demonstrate that the λ of carbonate and clastic specimens decrease strongly with increasing temperature. In contrast, the λ of intrusive and volcanic rocks are relatively insensitive to temperature. The temperature (T) dependence of λ can be classified into three groups in terms of the value of λ at 25°C. The first group is composed of rocks characterized by high λ (>4.5 W/m·K) at room temperature, for which the curves of λ−T exhibit a concave pattern. The second group consists of rocks with a moderate λ (2.5~3.5 W/m·K), in which the curves tend to be a straight line. The last group comprises rocks with a low λ (<2.5 W/m·K), exhibiting convex curves. There exists a close relationship between the λ at 25°C and its rate of decrease (α). The absolute value of α increases with the λ at 25°C rising. The relationship between the two values can be fitted by the equation y=ax+b1/x+c to derive the fitting parameters a, b, and c; by this equation with known fitting parameters, the λ of the deep carbonate rocks of the Tarim Basin have been estimated.